PERBANDINGAN PENGGUNAAN TEH KOTAK ORIGINAL DAN TEH KOTAK BLACKCURRANT SEBAGAI MEDIA KONTRAS ORAL NEGATIF TERHADAP INFORMASI ANATOMI PADA PEMERIKSAAN MRCP DI INSTALASI RADIOLOGI RSUP PROF. DR. R. D KANDOU MANADO - Ema, Ema Grivid Kuntag; Wulandari, Putu Irma; Sukadana, Kadek (Medical Imaging and Radiation Protection Research Journal, 2023)
The principle of using contrast media is to influence the magnetic field and relaxation times of T1 and T2. Contrast media in MRCP consists of positive and negative contrast media. Gadolinium is a positive contrast medium with intravenous injection, while the negative contrast medium used must contain manganese (Mn) or iron (Fe) (Westbrook et al, 2016). Research conducted by Suhardi et al (2013) states that the use of positive contrast media is increasingly rarely used due to the high price and difficult to obtain, it also has side effects on patients, such as weakness, nausea and vomiting. According to Fatimah et al (2018), natural ingredients with relatively high manganese (Mn) content that can be used as negative oral contrast media, one of which is the manganese content in packaged oolong tea, which is 0.9 mg. At the Radiology Installation of Prof. RSUP. DR. R. D. Kandou Manado by using boxed tea as a substitute for positive contrast media which is expensive and has side effects on patients.This type of research is a qualitative research with interview, observation and experiment methods. This study used the original box tea and blackcurrant box tea as negative oral contrast media to 3 volunteers. The examination was carried out twice for each volunteer, using the original box tea in the first week and blackcurrant box tea in the second week. The results of the images obtained will be asked for opinions through interviews with respondents, namely 1 radiology doctor and 2 radiographers. Data is processed using a coding system. MRCP examination procedure at Prof. RSUP. DR. R. D Kandou Manado includes patient preparation with the patient fasting 6 hours before the examination with the aim of avoiding fluid in the duodenum which can interfere with the biliary tract and bile duct into the duodenum. Instructions for drinking boxed tea contrast media were carried out 10-15 minutes before the examination, followed by preparation of equipment, patient position, protocol and examination technique. The resulting image does not provide a difference between the use of the original box tea and blackcurrant box tea on the anatomical image information on MRCP. The advantages of using negative oral contrast media, Teh Kotak, is able to help reduce signals from CBD and Vater's ampulla, as well as being able to display MRCP images that are better than using other negative contrast media. Patients with diabetes are not recommended to use this contrast medium.